Yield and quality of Avena sativa associated with Vicia sativa in the puna region of Peru - Arias A., Alberto (2021)
The study was conducted at the Alpaicayan Experimental Centre, Daniel Alcides Carrión National University, Pasco, Peru, with the objective of determining the forage production and nutritional quality of oats associated with vetch. Forage production was determined in green matter content (GM), dry matter (DM) and percent of dry matter (%DM). For the nutritional value, crude protein (%CP), neutral detergent fibre (%NDF), acid detergent fibre (%ADF), calcium (%Ca) and phosphorus (%P) were determined. The treatments were T-1 (Creole oat, 150 kg/ha), T-2 (Mantaro 15 oat, 110 kg/ha), T-3 (Mantaro 15 oat plus vetch, 110 and 30 kg/ha) and T-4 (creole oat plus vetch, 150 and 30 kg/ha). GM production indicated that T-1 and T-4 were similar but significantly greater than T-2 and T-3 (p<0.05); however, without significant differences in DM production between treatments. T-4 obtained the largest content of %PC, T-2 and T-4 presented greater yields of %NDF and %ADF. T-4 presented the highest content of %P, while there was no difference between treatments for the content of %Ca. It is concluded that the Mantaro 15 + vetch treatment has a better forage production and is of better nutritional quality in relation to the other treatments.